"It's Not Much of a Life": The Benefits and Ethics of Using Life History Methods With People Who Inject Drugs in Qualitative Harm Reduction Research. (June 2018) - Harris, Magdalena; Rhodes, Tim
A life history approach enables study of how risk or health protection is shaped by critical transitions and turning points in a life trajectory and in the context of social environment and time. We employed visual and narrative life history methods with people who inject drugs to explore how hepatitis C protection was enabled and maintained over the life course. We overview our methodological approach, with a focus on the ethics in practice of using life history timelines and life-grids with 37 participants. The life-grid evoked mixed emotions for participants: pleasure in receiving a personalized visual history and pain elicited by its contents. A minority managed this pain with additional heroin use. The methodological benefits of using life history methods and visual aids have been extensively reported. Crucial to consider are the ethical implications of this process, particularly for people who lack socially ascribed markers of a "successful life."